ADAPTASI BUDAYA MAHASISWA INDONESIA DALAM MENGHADAPI CULTURE SHOCK DI UNI EMIRAT ARAB - Kuntum Chaira; Nurul Mustaqimmah (Jurnal Sarjana Ilmu Komunikasi (J-SIKOM), 2026)
This study examines the cultural adaptation dynamics of Indonesian students facing culture shock in the United Arab Emirates (UAE), an environment blending religious identity with multiculturalism. Using a qualitative approach based on Oberg’s culture shock theory and Kim’s adaptation model, this research uncovers how students navigate cultural disorientation. Findings reveal that while shared religious values offer psychological comfort during the honeymoon phase, they cannot fully mitigate interactional barriers in the crisis phase caused by dialectal differences, contrasting social norms, and local communication styles. Ethnic community support and flexible interaction strategies mediate the recovery phase, ultimately culminating in the formation of a hybrid identity during the adjustment stage. Successful adaptation in the UAE depends on identity transformation, communicative competence, and emotional resilience, without losing one's cultural roots. This study provides practical insights for prospective international students navigating Middle Eastern social complexities. Keywords: Cultural Adaptation, Culture Shock, Intercultural Communication, Indonesian Students, United Arab Emirates